Scaling rice fish systems: decision support tools for tailoring and targeting investments - Smith, B.; Dubois, Mark (International Water Management Institute, 2023)
Spatial and analytical decision support tools can link decision-makers and other stakeholders across sectors, scales, and disciplines with end users to better understand outcomes and determine priorities for targeting investments to scale rice-fish systems.